A comparison of static and dynamic balance performance in adolescent male wrestlers and judoists - Gencay, O. A.; Gencay, S.; Gencay, E. (Science & Sports, 2020)
Objectives: The purpose of this study was to compare the dominant and non-dominant legs in respect of dynamic and static balance and to examine the effect of sport type, sportive experience and BMI on the static and dynamic balance of adolescent male judoists and wrestlers. The results of the study could be beneficial for the prevention of injury to the athletes and could be applied to training management.